2010
DOI: 10.1063/1.3496357
|View full text |Cite
|
Sign up to set email alerts
|

Cell rotation using optoelectronic tweezers

Abstract: A cell rotation method by using optoelectronic tweezers (OET) is reported. The binary image of a typical OET device, whose light and dark sides act as two sets of parallel plates with different ac voltages, was used to create a rotating electric field. Its feasibility for application to electrorotation of cells was demonstrated by rotating Ramos and yeast cells in their pitch axes. The electrorotation by using OET devices is dependent on the medium and cells' electrical properties, the cells' positions, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Recently, Liang et al, reported that both yeast cells and Ramos (lymphoma) cells underwent the translation and rotation motions simultaneously from the dark areas to the illuminated areas in an OET chip. 36 However, this rotation was performed in a rotational AC electric field. Our team has discovered that only specific types of cells (i.e., Melan-a cells, lymphocytes, and white blood cells) can self-rotate in an OET chip with a non-rotating AC electric field due to the physical properties of cells, such as the uneven distribution of mass within the rotating cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Liang et al, reported that both yeast cells and Ramos (lymphoma) cells underwent the translation and rotation motions simultaneously from the dark areas to the illuminated areas in an OET chip. 36 However, this rotation was performed in a rotational AC electric field. Our team has discovered that only specific types of cells (i.e., Melan-a cells, lymphocytes, and white blood cells) can self-rotate in an OET chip with a non-rotating AC electric field due to the physical properties of cells, such as the uneven distribution of mass within the rotating cells.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 3, the boundary condition for calculating the variation of e-field distribution within time domain (Figure 3a), the time-averaged e-field ( Figure 3b) and the micro flow pattern (Figure 3c) are presented. It is assumed that no current flows across the boundary between the illuminated and unilluminated regions in the a-Si:H layer because the impedance of conjunction is very large [22].The upper surface of EDL1 was set as bottom boundary surface of the computation domain for calculating the term Rerpϕ´ϕ s qp´E t˚q s in Equation (10). The EDL1 in the light and dark area was modeled by the boundary condition σ m Bϕ{Bz "`ϕ´V 0 e jpωt`ψ i q˘{ pR`jXq (it can also be equivalently expressed by another mathematical form of distributed impedance in COMSOL program), where σ m is the electrical conductivity of the bulk medium, ϕ is the potential phasor needing to be solved at the bottom boundary of fluidic chamber.…”
Section: Simulation and Analysis Of Electric Field And Flow Patternmentioning
confidence: 99%
“…Optical tweezers use a focused laser beam to manipulate microscopic objects and are capable of orienting single cells [14]- [18]. However, the optical tweezers technique is limited to rotating a cell about one axis [19].…”
Section: Introductionmentioning
confidence: 99%